2019
DOI: 10.1021/acs.biomac.9b00190
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Organocatalytic Synthetic Access to Statistical Copolyesters from l-Lactide and ε-Caprolactone Using Benzoic Acid

Abstract: The development of synthetic strategies to produce statistical copolymers based on L-lactide (L-LA) and ε-caprolactone (CL), denoted as P(LA-stat-CL), remains highly challenging in polymer chemistry. This is due to the differing reactivity of the two monomers during their ring-opening copolymerization (ROcP). Yet, P(LA-stat-CL) materials are highly sought-after as they combine the properties of both polylactide PLA and poly(ε-caprolactone) (PCL). Here, benzoic acid (BA), a naturally occurring, cheap, readily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 71 publications
(179 reference statements)
1
22
0
Order By: Relevance
“…Contreras et al [24] researched the use of zinc diphenyl as initiator to prepare PLCL block copolymers using sequential polymerization, and changed the ratio of comonomers to make them have a low dispersibility and a good ordering. Mezzasalma et al [25] found that using benzoic acid as a catalyst and various alcohols as initiators, PLCL copolymers with good molar mass and dispersibility can be prepared under solvent-free conditions. The elongation at breaking point of the synthesized PLCL copolymer could only reach to 485% [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Contreras et al [24] researched the use of zinc diphenyl as initiator to prepare PLCL block copolymers using sequential polymerization, and changed the ratio of comonomers to make them have a low dispersibility and a good ordering. Mezzasalma et al [25] found that using benzoic acid as a catalyst and various alcohols as initiators, PLCL copolymers with good molar mass and dispersibility can be prepared under solvent-free conditions. The elongation at breaking point of the synthesized PLCL copolymer could only reach to 485% [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…34,44 The transesterication reactions might be rather negligible due to the absence of various heterotraids. 34,45 In Fig. 8, a monomodal SEC curve of PCLA suggested the synthesis of block PCLA.…”
Section: Copolymerization Of 3-caprolactone and L-lactidementioning
confidence: 99%
“…To date, only few organocatalysts have been reported in the copolymerization in bulk manner. Benzoic acid accompanied with the alcohol initiator was proved to be active for copolymerization of 3-CL and L-LA mixture to obtain the PCLA at 155 C. 34 More than 24 h was required to reach reasonable conversion, apart from which, another equivalent catalyst was added along with the other monomer to obtain block copolymers. The dibenzoylmethane (DBM) was studied to catalyze the PCLA at 155 C, M n of which ranged from 1000 to 4100 g mol À1 , while long reaction time over 48 h was also inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] A series of aliphatic polyesters, including poly(lactide), poly(ε-caprolactone), poly(δ-valerolactone) and poly(γ-butyrolactone), have been successfully achieved with organocatalysts. [24][25][26][27][28][29] Despite the great successes achieved with organocatalysts in the ROP of cyclic lactones or lactides, the organocatalytic preparation of PLGA copolymers has been scarcely explored. Satoh and coworkers achieved the organocatalytic regioselective ring-opening polymerization (ROP) of optically active methylglycolides (MGs) to produce highly alternating PLGAs using an organophosphazene base tBu-P 2 as the catalyst.…”
Section: Introductionmentioning
confidence: 99%